2019
DOI: 10.1186/s13613-019-0541-8
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein (HDL) particle size and concentration changes in septic shock patients

Abstract: Background: Sepsis is associated with systemic inflammation that may impact lipoprotein function. In particular, high-density lipoproteins (HDLs) that display pleiotropic protective roles may be dysfunctional in septic conditions. The aim of this study was to evaluate the HDL profile and the inflammatory context in septic shock patients admitted to our intensive care unit (ICU). Methods: In this study, 20 septic shock patients and 20 controls (ICU patients without septic shock) were included. Plasma samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 48 publications
(52 reference statements)
1
60
0
1
Order By: Relevance
“…de la Llera et al have shown that LPS infusion in healthy volunteers led to a decrease of small-and medium-size particles without any change in the total number of HDL particles [72]. We have shown that HDL levels are dramatically decreased in the acute phase of septic shock and that there is a shift toward large HDL particles [86]. Another study underlined that both HDL size and HDL-C concentration were independently associated with coronary artery disease risk [87].…”
Section: Hdl Function In Inflammatory Statementioning
confidence: 49%
“…de la Llera et al have shown that LPS infusion in healthy volunteers led to a decrease of small-and medium-size particles without any change in the total number of HDL particles [72]. We have shown that HDL levels are dramatically decreased in the acute phase of septic shock and that there is a shift toward large HDL particles [86]. Another study underlined that both HDL size and HDL-C concentration were independently associated with coronary artery disease risk [87].…”
Section: Hdl Function In Inflammatory Statementioning
confidence: 49%
“…We have compared the lipid profiles between septic and trauma patients, two situations in which inflammation is exacerbated. HDL-C levels were markedly lower in septic patients relative to trauma patients, whose concentration was normal [69]. The mechanisms underlying this decrease in HDL plasma concentrations are not fully understood but could be due to an increased turnover paralleled by a reduced hepatic synthesis [70].…”
Section: Hdl-c Levels In Sepsis: What Do We Learn From Clinical Studies?mentioning
confidence: 94%
“…It has been suggested that distinct HDL subspecies have differential biological functions. For example, large HDL seems to be less anti-inflammatory [23,24], whereas small HDL subclasses may be enriched in either cargo or other components of HDL that are responsible for its alternative functions [25,26]. The summary of HDL functions in health and disease is presented in Figure 1.…”
Section: Hdl Role and Functionsmentioning
confidence: 99%